Pembentukan Koperasi Mahasiswa sebagai Implementasi Penguatan Kewirausahaan dan Ekonomi Kerakyatan di Lingkungan Perguruan Tinggi: Pengabdian - Muthowif Muthowif; Siti Lailatus Sofiyah; Mira Gayatri Kartika; Davis Febrinanto Prakasa; Wiwik Prihartanti; Agus Rahmanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Student cooperatives play a strategic role as a learning platform for entrepreneurship, strengthening the people’s economy, and fostering students’ economic independence within higher education institutions. However, limited understanding and participation in student cooperatives remain a challenge at Universitas W.R. Supratman Surabaya. This community service program aimed to establish the “Harmoni W.R. Supratman” Student Cooperative as an effort to strengthen entrepreneurial spirit and students’ economic independence. The activity employed a participatory-educative approach, including cooperative workshops, interactive discussions, and intensive mentoring for prospective cooperative members. The results indicate an improvement in students’ understanding of cooperative concepts, principles, and legal foundations, as well as the successful formation of the cooperative’s organizational structure and the drafting of its Articles of Association and Bylaws. Furthermore, the program fostered students’ independence, responsibility, and teamwork skills in managing campus-based economic organizations. In conclusion, this community service activity was effective in establishing a professional and sustainable student cooperative while contributing to the development of students’ entrepreneurial capacity and economic independence at Universitas W.R. Supratman Surabaya.